GAMBARAN POTENSI INTERAKSI OBAT PADA PASIEN SKIZOFRENIA DI RUMAH SAKIT UMUM SIAGA MEDIKA PURBALINGGA - Rosyadi, Anwar; Arifin, Muhamad Jaenal; Yunarti, Kresensia Stasiana (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2025)
Schizophrenia is a global mental health issue, with relapse often triggered by patient non-adherence to medication. The use of complex drug combinations risks causing drug interactions. Therefore, this study aimed to identify medication use patterns and potential drug interactions in outpatient schizophrenia patients at RSU Siaga Medika Purbalingga. This descriptive research utilized medical records and patient prescriptions from January to June 2024, with samples selected through purposive sampling. Drug interaction analysis was performed using Medscape and Drugs.com applications. The results show that potential drug interactions were categorized as major (15.28%), moderate (79.17%), and minor (72.73%). The most frequent major interaction was found in the combination of Clozapine and Risperidone (16.67%), which can lead to serious side effects such as cardiovascular issues, neuroleptic malignant syndrome, and prolonged QT interval.